2019
DOI: 10.1073/pnas.1912546116
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A light induces DNA damage and estrogen-DNA adducts in Fuchs endothelial corneal dystrophy causing females to be more affected

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a leading cause of corneal endothelial (CE) degeneration resulting in impaired visual acuity. It is a genetically complex and age-related disorder, with higher incidence in females. In this study, we established a nongenetic FECD animal model based on the physiologic outcome of CE susceptibility to oxidative stress by demonstrating that corneal exposure to ultraviolet A (UVA) recapitulates the morphological and molecular changes of FECD. Targeted irradiation of mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 63 publications
(87 reference statements)
2
88
0
2
Order By: Relevance
“…However, in the U.S approximately 4% of the population over the age of 40 years are diagnosed with FECD. Interestingly, females are more affected than males [ 23 ]. Typically, Asian populations show fewer cases of FECD [ 24 , 25 ].…”
Section: Fuchs Endothelial Corneal Dystrophymentioning
confidence: 99%
See 3 more Smart Citations
“…However, in the U.S approximately 4% of the population over the age of 40 years are diagnosed with FECD. Interestingly, females are more affected than males [ 23 ]. Typically, Asian populations show fewer cases of FECD [ 24 , 25 ].…”
Section: Fuchs Endothelial Corneal Dystrophymentioning
confidence: 99%
“…Loss of Nrf2 and thus the Nrf2 regulated oxidative stress response in FECD suggests that over an individual's lifetime the constant UV exposure accentuates CEC death to a pathological level. Evidence for which has been obtained from both in vitro studies [ 65 ], as well as an in vivo animal model of UV induced cornea damage [ 23 ]. Cultures of human CECs exposed to UVA have been demonstrated to upregulate both Nrf2 mRNA and result in the translocation of Nrf2 to the nucleus resulting in induction of the Nrf2 regulated genes NQO1 and HO-1 [ 65 ].…”
Section: The Role Of Oxidative Stress In the Pathogenesis Of Fecdmentioning
confidence: 99%
See 2 more Smart Citations
“…Under normal circumstances, ROS production is maintained at a homeostatic level due to the endogenous antioxidant defense systems, such as superoxide dismutase (SOD), thioredoxin peroxidase (TPX), catalase (CAT), and glutathione peroxidase (GSH-Px) [ 11 , 12 ]. However, excessive production of ROS or a reduced antioxidant capacity leads to an accumulation of ROS in intestinal mucosa or enterocytes, thus causing oxidative stress and damage to macromolecules, including DNA damage [ 13 , 14 ], protein adduction [ 15 ], and lipid peroxidation [ 16 , 17 ]. In vivo and in vitro studies have shown that ROS can trigger apoptosis of intestinal epithelial cells and impair the intestinal mucosal barrier in animals [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%